Audit Quality: A Bibliometric Analysis of Intellectual Structure and Research Fronts (2000–2026) - Loso Judijanto; Khairul Nur Adli (Westscience Press, 2026)
This study aims to map the intellectual structure and identify emerging research fronts in audit quality literature through a comprehensive bibliometric analysis covering the period 2000–2026. Data were collected from the Scopus database and analyzed using VOSviewer to examine co-authorship, co-citation, and keyword co-occurrence networks. The findings reveal that audit quality research is strongly rooted in multidisciplinary foundations, particularly within total quality management, healthcare quality, and procedural evaluation frameworks. The intellectual structure is characterized by several interconnected clusters, including quality management systems, empirical outcome-based studies, and methodological approaches. Temporal and density analyses further indicate a significant shift toward emerging themes such as audit quality as a distinct research domain, artificial intelligence, and technology-driven auditing practices. Despite this progression, the results also highlight a relative fragmentation between traditional and emerging themes, suggesting opportunities for greater integration in future research. This study contributes by providing a systematic overview of the evolution of audit quality research, identifying dominant themes, and outlining future directions that emphasize the integration of technological innovation with established theoretical frameworks.